Nanofatigue behaviour of single struts of cast A356.0 foam: cyclic deformation, nanoindent characteristics and sub-surface microstructure. (October 2020) - Schmahl, M.; Märten, A.; Zaslansky, P.; Fleck, C.
Abstract: Struts are the main load carrying elements in cyclically loaded open cell metal foams. Little is known about the local fatigue behaviour and the influence of the microstructure on nanoscale deformation mechanisms. Different to the bulk counterpart, the millimetre-sized struts in precision-cast AlSi7Mg0.3 foams contain only 1–2 Al-dendrites, Si-Al-eutectic and intermetallic phases. We applied cyclic nanoindentation to N = 10 5 to assess nanofatigue. The change in minimum depth per cycle and the ratio of minimum to maximum indentation depths versus the number of cycles correspond to cyclic plastic processes. These and the indent and pile-up morphologies were correlated with the microstructure and dislocation formations revealed by phase-contrast-enhanced micro-computed tomography and transmission electron microscopy. Our results reveal that Si-particles affect deformation within 5 to 10 μm from the indent, and that they favour the formation of fatigue induced dislocation cells in the affected volume. We believe that this interaction is mediated through residual stresses. Furthermore, local variations in microstructure strongly influence the cyclic deformation behaviour and the indent pile-up size and morphology. Interestingly, the results well coincide with observations during fatigue of the bulk alloy reported in the literature. Graphical abstract: Unlabelled Image Highlights: Millimetre-sized struts of a cast AlSiMg foam were cyclically nanofatigued up to 10 5 cycles. Quasi-static nanoindentation revealed inclusion effects on local properties. Silicon inclusions affected cyclic properties at a distance of 5 to 10 μm. Nanocyclic deformation behaviour was strongly affected by residual stress release. We observed significant hardening for N ≦ 10 3 . Hardening decreased for N ≧ 10 4, sometimes down to saturation.